Acute hyperhydration reduces athlete biological passport OFF-hr score - Bejder, J.; Hoffmann, M. F.; Ashenden, M.; Nordsborg, N. B.; Karstoft, K.; Mørkeberg, J. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Anecdotal evidence suggests that athletes hyperhydrate to mask prohibited substances in urine and potentially counteract suspicious fluctuations in blood parameters in the athlete biological passport (ABP). It is examined if acute hyperhydration changes parameters included in the ABP. Twenty subjects received recombinant human erythropoietin (rhEPO) for 3 weeks. After 10 days of rhEPO washout, 10 subjects ingested normal amount of water (~ 270 mL), whereas the remaining 10 ingested a 1000 mL bolus of water. Blood variables were measured 20, 40, 60, and 80?min after ingestion. Three days later, the subjects were crossed-over with regard to water ingestion and the procedure was repeated. OFF-hr was reduced by ~ 4%, ~ 3%, and ~ 2% at 40, 60, and 80 min, respectively, after drinking 1000?mL of water, compared with normal water ingestion (P < 0.05). Forty percent of the subjects were identified with atypical blood profiles (99% specificity level) before drinking 1000 mL of water, whereas 11% (n = 18), 10% and 11% (n?=?18) were identified 40, 60, and 80 min, respectively, after ingestion. This was different (P?<?0.05) compared with normal water intake, where 45% of the subjects were identified before ingestion, and 54% (n = 19), 45%, and 47% (n = 19) were identified 40, 60, and 80?min, respectively, after ingestion. In conclusion, acute hyperhydration reduces ABP OFF-hr and reduces ABP sensitivity.